Investigation of Heat Conduction Through PMC Components Made Using Resin Transfer Moulding - Sakka, Aymen (Université d'Ottawa / University of Ottawa, 2012)
The increasing demand for polymer matrix composites (PMCs) from the airframe industry raises the issues of productivity, cost and reproducibility of manufactured PMC components. Performance reproducibility is closely related to the manufacturing technique. Resin transfer moulding (RTM) offers the advantage of flexible manufacturing of net-shape PMC components with superior repeatability starting from ready-to-impregnate dry reinforcements. An RTM apparatus was developed for manufacturing PMC plates and demonstrator components representative of actual, PMC components and PMC moulds made and used in the airframe industry. The RTM process developed in this work involved making net-shape dry carbon fibre preforms and impregnating them an epoxy resin, targeting mould applications. Thermal repeatability of different net-shape PMC components manufactured using the RTM apparatus developed in-house was investigated. Effects of bonding an outer copper plate onto the PMC material, targeting mould applications known as integrally heated copper tooling (IHCT), were explored. Heat conduction through the PMC components was studied using simulation models validated by experimental data obtained primarily by thermography. Manufactured PMC components showed good repeatability, particularly in terms of thermal behaviour. The IHCT technique was found to be well suited for mould applications. Expected advantages of thermography were materialised. Finally, the simulation models developed were in good agreement with experimental data.
Keywords: Composites; Resin transfer moulding (RTM); Preforming; Carbon fibre; Polymer matrix composites (PMC); Thermography